2020
DOI: 10.1109/access.2020.2994085
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Contact Resistance of Contact Bodies With Cambered Surface

Abstract: The electrical contact resistance of cambered surface contact is systematically studied by analytical solution and finite-element simulation. Two representative cambered surface contacts, namely sphere-plane contact and cylinder-plane contact are built and the distributions of electrical current lines profile and isopotential are compared explicitly. Subsequently, the effects of size parameters of cambered surface and mechanical load on contact resistance are evaluated over a large range of aspect ratios. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Concerning the data presented in [ 18 ], it can be noted that the experimental results were between the two analytical calculations (Holm and Greenwood). Additionally, from the point of view of the relationship between contact resistance and the area of contact, similar variation results were reported by Shujuan et al [ 13 ], Ren et al [ 14 ], Lim et al [ 15 ], and Su et al [ 24 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Concerning the data presented in [ 18 ], it can be noted that the experimental results were between the two analytical calculations (Holm and Greenwood). Additionally, from the point of view of the relationship between contact resistance and the area of contact, similar variation results were reported by Shujuan et al [ 13 ], Ren et al [ 14 ], Lim et al [ 15 ], and Su et al [ 24 ].…”
Section: Discussionsupporting
confidence: 85%
“…Numerous studies on contact resistance and electrical contacts have made mention of Greenwood’s and Holm’s analytical model for contact resistance calculation [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. The research reported in this paper used Holm’s and Greenwood’s models to calculate the contact resistance.…”
Section: Analytical Models For Contact Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…    As mentioned above, the corresponding ωc at the inception of the elastic-plastic deformation regime can be determined by using Equation (4). Additionally, the corresponding * p  at the end of elastic-plastic deformation regime can be determined by using Equation (14). Furthermore, to estimate the contact parameters of the elastic-plastic range, the empirical formula is proposed in this work as follows:…”
Section: Elastic-plastic Rangementioning
confidence: 99%
“…Contact between two rough surfaces can be equivalent to contact between a hemisphere and a rigid flat [11][12][13]. The study of elastic-plastic contact behavior between hemisphere and a rigid flat is of great significance to the analysis of electrical contact [14][15][16][17], friction [18,19], and wear [20,21] between two rough surfaces.…”
Section: Introductionmentioning
confidence: 99%